PERAN FREKUENSI RAPAT KOMITE AUDIT DAN INDEPENDENSI KOMITE DALAM MENINGKATKAN KUALITAS PELAPORAN KEUANGAN DI SKTOR INFRASTRUKTUR - Prastyawati, Tika; Anshari, Rahman; Pribadi, Muhammad Iqbal (STIE Mahardhika, 2025)
The level of responsibility and transparency of a company is reflected in the quality of its financial reporting, especially in the infrastructure industry which faces significant financial risks and involves large-scale projects. This study aims to investigate the effect of audit committee independence and meeting frequency on the quality of financial reporting in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2023. The methodology used in this research is quantitative with a multiple linear regression analysis approach. The sample determination was carried out using purposive sampling method, which resulted in 108 observation data. The findings of the analysis show that the frequency of audit committee meetings has a significant and positive effect on the quality of financial reporting, while the level of independence of the audit committee does not show a significant impact. These results indicate that, compared to committee independence, the intensity of audit committee meetings has a greater influence in improving the effectiveness of supervision and accuracy of financial statement presentation. This research reinforces the active role of audit committees as part of the corporate governance mechanism, both theoretically and practically.